2018
DOI: 10.1177/1179069518789149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monoamines and Antidepressants on Astrocyte Physiology: Implications for Monoamine Hypothesis of Depression

Abstract: Major depressive disorder (MDD) is one of the most common neuropsychiatric disorders affecting over one-fifth of the population worldwide. Owing to our limited understanding of the pathophysiology of MDD, the quest for finding novel antidepressant drug targets is severely impeded. Monoamine hypothesis of MDD provides a robust theoretical framework, forming the core of a large jigsaw puzzle, around which we must look for the vital missing pieces. Growing evidence suggests that the glial loss observed in key reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 87 publications
1
28
0
Order By: Relevance
“…The hippocampus in the brain manages human learning, memory, and emotional cognition. A large number of preclinical and clinical studies have shown that depression is associated with the lack of monoamine neurotransmitters in the hippocampus, and regulating monoamine concentrations can ease symptoms of depression [16]. In order to study the effect of TIV on the neurotransmitter between brain and intestine, we mainly studied the brain-gut peptides with double distribution of brain and intestine.…”
Section: Resultsmentioning
confidence: 99%
“…The hippocampus in the brain manages human learning, memory, and emotional cognition. A large number of preclinical and clinical studies have shown that depression is associated with the lack of monoamine neurotransmitters in the hippocampus, and regulating monoamine concentrations can ease symptoms of depression [16]. In order to study the effect of TIV on the neurotransmitter between brain and intestine, we mainly studied the brain-gut peptides with double distribution of brain and intestine.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may manifest itself through reduced glutamate uptake, diminished trophic support or disruption of metabolic coupling (Elsayed and Magistretti, 2015;Marathe et al, 2018;Martin et al, 2013).…”
Section: Astrocytic Atrophy As a Potential Pathogenic Eventmentioning
confidence: 99%
“…Although neuronal and spine atrophy has been thought to underlie the volume reduction (Duman and Duman, 2015;Qiao et al, 2016;Sheline, 2003;Sousa et al, 2000), increasing evidence supports the involvement of astrocytes in the volumetric loss (Cobb et al, 2016;Czéh et al, 2005;Naskar and Chattarji, 2019;Rajkowska and Stockmeier, 2013;Rajkowska et al, 1999) and the pathophysiology of depression (Elsayed and Magistretti, 2015;Marathe et al, 2018). Astrocytes are profoundly affected as a result of depression, resulting in significant atrophy (Cobb et al, 2016;Cotter et al, 2001;Miguel-Hidalgo et al, 2000Ongür et al, 1998;Rajkowska and Stockmeier, 2013;Rajkowska et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the release of the above tropic factors by astrocytes is dependent on extracellular monoamines concentration. Given that, it was proposed that antidepressant medication may also act via this pathway, which incorporates astrocytes into the classical monoamine hypothesis of antidepressants' action (2). For instance, secretion of BDNF, VEGF and VGF are increased by monoamines and by antidepressants which increase monoamines levels (68).…”
Section: Astrocytes-neuron Crosstalk and Depressionmentioning
confidence: 99%
“…It is becoming clear that glia abnormalities have a crucial role in the neuroinflammatory pathophysiology of those disorders. MDD is also accompanied by volumetric brain reduction and a decrease in metabolic activity mostly in the hippocampus and medial prefrontal cortex (mPFC) and it is becoming evident that those changes are not only due to neuronal atrophy but also abnormalities in non-neuronal glial cells contribute to those changes (2).…”
Section: Introductionmentioning
confidence: 99%